15 years of pension reform in Germany: old successes and new threats - Holger Bonin (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
The paper surveys the state of German pension system after a sequence of reforms aimed at achieving long-term sustainability. We argue that the latest reforms have moved pension provision in Germany in principle from a defined benefit to a defined contribution scheme, and that this move has stabilized pension finances to a large extent. We furthermore argue that the real economy consequences of global financial create threats to the core success factors of the reforms - cutting pension levels and raising mandatory pension age. Finally the paper discusses further possible reform measures, including the option to install a fourth pillar providing income in retirement through working after pension age.
Keywords: H55; J11; 330; Pension Financing; Financial Crisis; Fiscal Sustainability Survey; Germany; Gesetzliche Rentenversicherung; Rentenreform; Rentenfinanzierung; Nachhaltigkeit; Finanzmarktkrise; Finanzmarktkrise; Deutschland